The Influence of Portal Deviation on the Effect of Repeat Dearterializations of a Transplantable Adenocarcinoma to the Rat Liver. Issue 1 (1994) - Wang, L. Q.; Persson, B. G.; Bengmark, S.
Abstract : As liver tumours receive some of their blood supply from the portal vein, we wanted to illustrate the influence of portal blood flow in combination with dearterialization in the treatment of liver tumours. Forty male, inbred Wistar/Furth rats with an adenocarcinoma transplanted to the liver were treated with various inflow occlusions repeated daily for 5 days. Deviation of the portal blood flow alone with an end-side porto-caval shunt did not alter the tumour growth ( p = 0.089). Thirty min of repeat dearterializations was potentiated by portal deviation so that tumour growth was delayed ( p = 0.004). However, repeat dearterializations for 60 min in portal deviated rats induced irreversible liver damage and all rats died in a few days. Repeated dearterializations for 60 minutes alone retarded the tumour growth as efficiently ( p = 0.007). Simultaneous occlusion of the hepatic artery and the portal vein for 30 minutes with a side-side porto-caval shunted (total devascularization) did not affect tumour growth ( p = 0.154). Liver aminotransferases (ASAT and ALAT) were substantially increased following dearterialization for 30 min in rats with either an end-side or a side-side porto-caval shunt. Dearterialization for 60 min in rats with end-side porto-caval shunts gave a further release of ASAT and ALAT. In conclusion, portal deviation did not augment the therapeutic benefit of repeat dearterializations for the treatment of this experimental liver tumour. Repeat dearterializations alone seemed to be a feasible and efficient therapy for liver tumours.